Novel association of familial testicular germ cell tumor and autosomal dominant polycystic kidney disease with PKD1 mutation. Issue 1 (31st August 2016) - Truscott, Laurel; Gell, Joanna; Chang, Vivian Y.; Lee, Hane; Strom, Samuel P.; Pillai, Rex; Sisk, Anthony; Martinez‐Agosto, Julian A.; Anderson, Martin; Federman, Noah
Abstract: Adolescent brothers were diagnosed with testicular germ cell tumors within the same month. Both were found to have multiple renal cysts on pretreatment imaging done for staging. The proband, his brother, and their mother, were all found to have a novel splice variant in intron 8 of the PKD1 gene by clinical exome sequencing. This is the second family reported with both familial testicular germ cell tumor (FTGCT) and autosomal dominant polycystic kidney disease (ADPKD), and the first described association of FTGCT with a splice variant in PKD1 . We suggest that this novel variant in PKD1 may convey increased risk for FTGCT in addition to causing ADPKD.